Answer:
(0,1) , (2,4) , (4,7)
Explanation:
convert the equation into slope-intercept form (this would be y=3/2x+1)
now plug in random numbers for x and solve for y by multiplying them by 3/2 and adding 1.
Answer:
A is $490 and B is 3990
Step-by-step explanation:
The way I solved this is with my last brain cells, you welcome.
2.8-(-5.1)
-(-5.1)=5.1
2.8+5.1= 7.9
Is this what you were asking?
An inverse function is a function that reverses another function, so we have a function called:
![p(x)](https://tex.z-dn.net/?f=p%28x%29)
Then, the inverse function will be as follows:
![p^{-1}(x)](https://tex.z-dn.net/?f=p%5E%7B-1%7D%28x%29%20)
Given that
![y = p(x)](https://tex.z-dn.net/?f=y%20%3D%20p%28x%29)
, we need to isolate x in terms of y:
![y = x^{2} -9](https://tex.z-dn.net/?f=y%20%3D%20%20x%5E%7B2%7D%20-9)
∴
![y+9 = x^{2}](https://tex.z-dn.net/?f=y%2B9%20%3D%20x%5E%7B2%7D)
So:
![x=+\sqrt{y+9}](https://tex.z-dn.net/?f=x%3D%2B%5Csqrt%7By%2B9%7D)
and
![x=-\sqrt{y+9}](https://tex.z-dn.net/?f=x%3D-%5Csqrt%7By%2B9%7D)
therefore, exchanging variables x and y:
![y=+\sqrt{x+9}](https://tex.z-dn.net/?f=y%3D%2B%5Csqrt%7Bx%2B9%7D)
and
![y=-\sqrt{x+9}](https://tex.z-dn.net/?f=y%3D-%5Csqrt%7Bx%2B9%7D)
![p^{-1}(x)=+\sqrt{x+9}](https://tex.z-dn.net/?f=p%5E%7B-1%7D%28x%29%3D%2B%5Csqrt%7Bx%2B9%7D)
and
![p^{-1}(x)=-\sqrt{x+9}](https://tex.z-dn.net/?f=p%5E%7B-1%7D%28x%29%3D-%5Csqrt%7Bx%2B9%7D)
Which are the figures shown below.
False. That does not satify the equation